Pengaruh Training Kognitif Terhadap Kemampuan Kognitif Pada Lansia Di Desa Sobokerto Kecamatan Ngemplak Boyolali - Prasaja Prasaja; Maharso Adi Nugroho (Interest : Jurnal Ilmu Kesehatan, 2018)
Background: The elderly phase is the last stage of development over every human life span. The process starts as infant phase followed by children, adults, old and elderly. Thorough out the elderly phase, there are significant decreases of tissue functions, yet it hampers the ability for body to repair any possible body damages. The decreasing functions in the elders, especially the cognitive functions would affect their functional independence in the long run. Method: A quantitative pre-experimental design with type one-group pre test-post test that compared the average scores between pre and post cognitive training, with no any control-group involved. The sampling technique used was purposive. Inclusion criteria were elders above 60 years old with good level of consciousness (place, time, person), and have no severe cognitive problems. The purpose of the research is to identify the effect of cognitive training on cognitive ability of the elders in Sobokerto Village Ngemplak Boyolali subdistrict and also to depict the elders’ population demographic based on age, gender and education. Data analysis was done with the use of quantitative analysis of paired sample t-test as the data is normally distributed. Sources of research data are presented in the form of: (1) primary data from examination results by using MMSE instruments, (2) secondary data from archives and documents. The techniques used to collect data were plain tests, observations and document studies. The outcome of the research is cognitive training module used thorough out the intervention programs. Result: this study are: (1) There is a clear evidence of positive result of cognitive training on cognitive ability of the elders (p = 0.001), (2) age distribution of elderly in Sobokerto Village Ngemplak subdistrict Boyolali Regency were dominated by age of <75 years (66.7%), (3) the total population of the elders in Sobokerto Village, Ngemplak sub-district, Boyolali regency are (83.3%), (4) the education level amongst the elders in Sobokerto village, Ngemplak sub-district, Boyolali regency are mostly junior high school (38.9%). Conclusion : There was a positive influence and significant cognitive training on cognitive abilities of the elderly in the village of Sobokerto Ngemplak Boyolali